Effect of Systemic Inflammation on Rat Attentional Function and Neuroinflammation: Possible Protective Role for Food Restriction - Yegla, Brittney; Foster, Thomas (Frontiers in Aging Neuroscience, 2019)
Background: Aging is characterized by subtle cognitive decline, which correlates with increased peripheral inflammation. Acute activation of the peripheral immune system, via lipopolysaccharide (LPS) injection, elicits deficits in hippocampal-dependent spatial memory. Little is known concerning the effect of chronic inflammation on prefrontal cortex (PFC)-dependent vigilance. We examined the impact of repeated LPS injections in young and middle-age rats on the 5-choice serial reaction time task (5-CSRTT), expecting repeated LPS treatment to induce attentional deficits with greater disruption in middle-age. Methods: Male Fischer-344 rats, 4- and 12-month-olds, were food restricted and trained on the 5-CSRTT. Once rats reached criterion, they were injected with LPS (1mg/kg, i.p.) weekly for four weeks and testing started 48hrs after each injection. To examine the possibility that mild food restriction inherent to the behavioral task influenced inflammation markers, a second group of food-restricted or ad-lib-fed rats was assessed for cytokine changes 48hrs after one injection. Results: Performing LPS-treated rats exhibited a sickness response, manifesting as reduced initiated and completed trials during the first week but recovered by the second week of testing. After the first week, LPS-treated rats continued to exhibit longer response latencies, despite no change in food retrieval latency, suggestive of LPS-induced cognitive slowing. Similarly, LPS-induced impairment of attention was observed as increased omissions with heightened cognitive demand and increased age. Repeated LPS-treatment increased the level of PFC IL-1α, and PFC IL-6 was marginally higher in middle-age rats. No effect of age or treatment was observed for plasma cytokines in performing rats. Histological examination of microglia indicated increased colocalization of Iba1+ and CD68+ cells from middle-age relative to young rats. Examination of food restriction demonstrated an attenuation of age- and LPS-related increases in plasma cytokine levels. Conclusions: Systemic inflammation, induced through LPS treatment, impaired attentional function, which was independent of sickness and exacerbated by increased cognitive demand and increased age. Additional studies revealed that food restriction, associated with the task, attenuated markers of neuroinflammation and plasma cytokines. The results emphasize the need for improved methods for modeling low-level chronic systemic inflammation to effectively examine its impact on attention during aging.